How to help a clumsy child : strategies for young children with developmental motor concerns - Kurtz, Lisa A. (Jessica Kingsley Publishers, 2003)
When a child has a developmental delay affecting motor coordination and development the ramifications are far reaching, from the daily tasks of dressing and brushing your teeth, to learning to write and participating in sports. How to Help a Clumsy Child is a practical resource manual and 'how to help' book for parents of, or professionals working with, young children with motor coordination developmental delays. It covers a range of topics, including recognizing normal and abnormal motor development, when and how to seek help, an overview of approaches used to help the clumsy child, and speci.